Review of Facilities for Low-Income Countries : Proposals for Implementation. (Policy Papers; Policy Paper ;, 2013)
Based on the Executive Board's guidance during the first stage of the Review of Low Income Countries (LIC) Facilities, this paper suggests a number of refinements to the facilities and instruments that are consistent with the self-sustainability of the Poverty Reduction and Growth Trust (PRGT). The proposals seek to improve the tailoring and flexibility of Fund support. Taken together with those advanced in the parallel paper on PRGT eligibility, they are projected to keep the average annual demand for PRGT resources within a range consistent with the Board's approved strategy to make the PRGT self-sustaining over the period 2013-35. The proposals are as follows.